Empfehlungen zur Malariaprophylaxe - Rothe, Camilla; Rosenbusch, Deike; Alberer, Martin; Bühler, Silja; Burchard, Gerd; Erkens, Kai; Feldt, Torsten; Grobusch, Martin P.; Köhler, Carsten; Kapaun, Annette; Löbermann, Micha; Meischner, Karin; et al. (Flugmedizin, Tropenmedizin, Reisemedizin, 2020)
Thieme E-Books & E-Journals